Analysing The Law For Termination Of Employment During Pregnancy Or Maternity Leave In Brics Countries (International Journal of Environmental Sciences, 2025)
This article examines the legal framework surrounding the dismissal of pregnant women in BRICS Countries including recently amended. It highlights key provisions in the Constitution, Labour Law, and other relevant statutes that protect pregnant employees. The analysis includes significant ILO reports on gender discrimination.The dismissal of pregnant women from employment is a critical issue, intersecting with rights to equality, non-discrimination, and protection of motherhood. This article delves into these legal provisions and examines pertinent case laws to elucidate the practical application and enforcement of these protections.